Expansion de l'agglomération de Lima et différenciation de l’espace résidentiel : analyse exploratoire d’un corpus de données diversifié - Marie Piron (Unité Mixte de Recherche 8504 Géographie-cités, 2015)
The forms of socio-spatial differentiation found in Lima are for the most part in line with the model of Andean metropolises. There is, for example, an opposition between central areas occupied by the middle and upper classes and the more recent and lower-class areas in the peripheries. There is also a directional expansion of the wealthier areas, in this case, towards the east of the central areas. This model is still very pronounced but seems to have changed since the end of the last century with internal diversification of previously homogeneous units. Our objective is to understand the current spatial organization of social differentiation in Lima. On the basis of data of the last national census of population in 2007 and of a set of aerial photos and satellite images taken since the middle of the 20th century, we build on, at the level of the blocks, various cartographical and statistical indicators concerning the successive layers of the expansion of Lima and its current socio-spatial structure. We conclude from this first, that the urban area is organized according to a scale of social and urban integration which is registered spatially on a gradient, from the center towards the peripheries, in correlation with the time the blocks were built. In a second phase, a series of multidimensional statistical analyses which visually reintroduce each block allows us to moderate this conclusion by the means of the study of the variability inside each layer of expansion. It is thus possible to understand the current territorial dynamics and to formulate the hypothesis of a change in the structure contrasting the center and the peripheries.